Comparative Analysis of Anesthesia-Related Complications: Recovery Profiles, and Psychosocial Outcomes in Gynecomastia Surgery Local Anesthesia versus General Anesthesia. - Amiruddin, Muhammad Usman; Hassan, Tauseef ul; Irshad, Sidra; Ali Adnan, Muhammad; Sadikan, Muhammad Zulfiqah; Jahangir, Jawad (Journal of Neonatal Surgery, 2025)
Background: Gynecomastia, a condition characterized by the enlargement of breast tissue in males, can have significant physical and psychological implications for affected individuals. Surgical intervention is often sought to alleviate symptoms and improve quality of life. The choice of anaesthesia plays a crucial role in gynaecomastia surgery,having a great impact-in determining patient outcomes.The selection of anesthesia type can impact various aspects of patient care, including anesthesia-related complications, recovery profiles and psychosocial outcomes. Understanding the differences between local and general anesthesia in the context of gynecomastia surgery is essential for optimizing patient care and improving surgical outcomes. Objective: This study aimed to compare anesthesia-related complications, recovery profiles, and psychosocial outcomes in patients undergoing gynecomastia surgery under local anesthesia versus general anesthesia. Methods: This comparative cross-sectional analytical study was conducted at UA Aesthetics Clinic Lahore from March 2023 to January 2025. It included 153 male patients undergoing gynecomastia surgery. Patients were divided into two groups: Group A underwent surgery under local anesthesia with or without sedation (n=76), and Group B underwent surgery under general anesthesia (n=77). Data were collected on demographics and clinical characteristics, anesthesia-related complications, intraoperative and postoperative outcomes, and psychosocial parameters. Results: Baseline characteristics were comparable between groups. Anesthesia-related complications were significantly higher in the general anesthesia group, including postoperative nausea and vomiting (14.3% vs. 3.9%), hemodynamic instability (11.7% vs. 2.6%), and airway-related sore throat (9.1% vs. 0%). Recovery outcomes favored local anesthesia, with earlier ambulation (2.4 ± 0.6 vs. 4.9 ± 1.1 hours, p<0.001), shorter hospital stay (0.9 ± 0.2 vs. 1.7 ± 0.4 days, p<0.001), and lower postoperative pain scores at all measured intervals. Psychosocial outcomes were positive in both groups, but local anesthesia patients reported higher early satisfaction (89.5% vs. 78.2%, p=0.04) and greater improvements in quality of life. Conclusion: It is concluded that local anesthesia is a safer and more effective option than general anesthesia for gynecomastia surgery, offering fewer complications, faster recovery, and enhanced short-term psychosocial satisfaction..